Dietary levels of potassium for broiler chickens - Oliveira,JE (2005)
Three experiments were conducted to determine the nutritional requirements of potassium (K) for male Ross broiler chickens, from 8 to 21, 22 to 42 and 43 to 53 days of age. The following parameters were evaluated: body weight gain (BWG), feed intake (FI) and feed conversion ratio (FCR). In each experiment, a completely randomized experimental design was used, with six treatments (K levels), and six, eight and eight numbers of replicates, and eight, five and four birds per pen, respectively. The experimental diets were basal diets deficient in K but supplemented with K carbonate to result in levels of 0.30, 0.44, 0.58, 0.72, 0.86 and 1.00% K. Estimated requirements for BWG were 0.628, 0.714 and 0.798% K, for the periods 8-21, 22-42 and 43-53 d, respectively.